PARADIGMA BARU PENDIDIKAN KONTEMPORER DI INDONESIA - Colle Said (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2019)
Education is a series of processes of human empowerment towards maturity, both intellectually, mentally and morally, to carry out the humanitarian function carried as a servant (abd) in front of his Khaliq and as a